Influência do teor de silício na usinabilidade da liga de alumínio 6351 - avaliada através de força de corte e acabamento superficial - Cunha, Daniel Fernandes da (2012)
The aim of this work is to study the effect of silicon content in the machinability of CBA s (Compania Brasileira de Aluminio) 6351 aluminum alloy measured through cutting force and surface finish. In a first moment the effect of depth of cut (ap), cutting speed (vc), feed rate (f) and silicon content (% Si) on the machinability were investigated. The machining process used was turning operation with no cutting fluid. In a second part of the tests it was used MQF (60 l/h) and over head flood in experimental tests with constant depth of cut. For each set of parameters it was acquired values of cutting forces and surface roughness with two repetitions, adopting a 3k design of experiments. The results showed that the silicon content has significant effect in the machinability of the studied alloy compared to the others parameters investigated. Keywords: